(untitled) - Gabaldon, Diana (New York, 2017)
"A collection of seven short stories set in the Outlander universe, never before published together, including two original stories and featuring ... Jamie Fraser"--
Keywords: Fraser, Jamie (Fictitious character); Fiction; Time travel; Fiction; Historical fiction